Observing the determinants of the psychotherapeutic process in depressive disorders. A clinical case study within a psychodynamic approach - Oasi, Osmano (Frontiers in Psychology, 2015)
This paper focuses on the relationship between depressive disorders, personality configurations, and mental functioning. A years treatment of a young man with the diagnosis of Depression is presented: the clinical and empirical points of view are described in depth through an assessment at the beginning and at one year after of an oriented psychodynamic psychotherapy. SCID I and II and HAMRS were administered to the patient in assessement phase. In the same phase he filled in BDI-II, and DEQ; the psychotherapist completed SWAP-200. These clinician instruments were used again after one year of the treatment. The PDM point of view is also presented. All sessions are audiotaped: twelve verbatim transcripts were coded with the Defense Mechanisms Rating Scale and CCRT. The results show a decrease in depressive symptoms, a change in some personality configurations, but a substantial invariance of the introjective profile, and a modification in mental functioning.